Dynamic analysis of complex spacial frame systems by the finite element method - Ve, Nguyen Ngoc (Vietnam Journal of Mechanics, 1986)
Numerical simula1ion of complex special frame systems subjected to static load dynamic load and base acceleration is formulated. A finite element model is applied therein the, complex nodes and the foundation influence are considered. Equations of motion are soviet afterontively by step-by-step direct integration and mode superposition method. A number of illustrated  example are computed by the numerical superpose FRADYN), which can be used directly in the field of staeciural design.